Deskripsi Kemampuan Berpikir Tingkat Tinggi Siswa dalam Menyelesaikan Soal Fungsi Kelas X SMAN 2 Tanjungpinang - Syarfina Witri; Febrian Febrian; Linda Rosmery Tambunan (Jurnal Gantang, 2019)
This study aims to describe the thinking ability of class X MIA 2 of SMA Negeri 2 Tanjungpinang in solving functional problems. research subjects A total of 40 students who have received material before function. Instrument for the assessment of students higher-order thinking skills, consisting of 10 questions. Data were analyzed using the average method as an explanation of students higher-order thinking skills. Considering the high level of students in terms of high-level thinking ability indicators, namely analyzing, understanding and creating. The results obtained are the average analysis indicator obtained is 47.85 with enough categories, the indicator analyzes with an average of 12.50 categories is very less. And the indicators created with an average of 19.02 with very less categories Keywords: deskription, higher order thinking skill